Age determination by magnetic resonance imaging of the wrist in adolesecent male football players - Dvorak, J.; George, J. (2007)
In football there are established age-related tournaments for males and females to guarantee equal chances within the game for all the different age groups. To prevent participation in the incorrect age group, and owing to the fact that in some Asian and African countries registration at birth is not compulsory, other methods of age determination need to be available. Standard radiographs of the left wrist have been used for assessment of skeletal age for many years. This is, however, not ethical in the sporting environment.